QUALITY ASSURANCE COURSES IN VET (VOCATIONAL EDUCATION AND TRAINING) FOR TOURISM ORGANISED BY THE CENTRE FOR TOURISM TRAINING - IRIMIEA, Silvia; ŞERBAN, Adriana (Studia Universitatis Babeș-Bolyai Geographia, 2015)
Quality Assurance Courses in VET (Vocational Education and Training) for Tourism Organised by the Centre for Tourism Training. The article seeks to give utterance to the findings of the pilot course on quality assurance designed and organised by the Centre for Tourism Training (CTT) as part of the AQUA.TS European Lifelong Learning project. The CTT has become involved in research and exchange of experience in the field of quality assurance driven by the educational policy-related background set out by the European documents and tools, including EQARF, EQAVET, the principles of lifelong learning and adult education. The main theoretic background to the present paper was assured by the European Commission documents regarding quality assurance in VET, while the experience and good practices acquired by the CTT have profoundly marked its quality assurance–oriented policy. Against this background, The Centre for Tourism Training (CTT) of the Faculty of Geography, University Babes-Bolyai, Romania, delivered a pilot training course on Quality Assurance in VET during 16 March and 10 April 2015. The training consisted of a theoretical knowledge-building module (16.03. 2015 - 27.03. 2015) and a practical module (30.03.2015 -10.04.2015), the latter focused on the use of the AQUA.TS TOOLKIT, an IT device aimed at the self-evaluation of the quality of performance of trainers and training providers, whose efficiency was tested during the organised training program.